UPM chemist receives Malaysian Institute of Chemistry Gold Medal Award - Juferi, Noor Eszereen (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
SERDANG, January 9 – Prof. Datuk ChM. Ts. Dr. Taufiq Yap Yun Hin, a lecturer from the Department of Chemistry, Faculty of Science, Universiti Putra Malaysia (UPM), has been awarded the Malaysian Institute of Chemistry (IKM) Gold Medal Award, presented by the IKM President, Datuk ChM. Dr. Soon Ting Kueh at the Chemistry Night Ceremony recently.